Reconceptualizing Light Propagation Through Augmented Newtonian Dynamics - Mavani, Krishi D. (Journal of Educational Research and Policies, 2025)
Augmented Newtonian Dynamics (AND) offers a new theory on the nature of light and electromagnetic radiation (EMR), presenting an aether-based framework that extends traditional Newtonian principles into the sub-atomic realm. Unlike conventional theories, which treat light as a purely quantum phenomenon or a wave propagating through space, AND proposes that EMR is mediated by a dynamic aether—a fundamental, photon-based medium that permeates the universe. This aether, emerging from the high-energy conditions following the Big Bang, is not merely a passive entity, but an active and evolving structure that influences the behavior of light and energy across cosmic scales. Through this lens, AND reinterprets the interactions of light with matter, offering new insights into the propagation of photons and the discrete nature of electromagnetic radiation. By grounding its principles in the origins of the universe AND provides a fresh framework that aligns with both observed electromagnetic phenomena and the broader evolution of cosmic structures.